2015
DOI: 10.1016/j.paid.2014.10.033
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences in the regulation of positive emotion: The role of attachment and self esteem

Abstract: a b s t r a c tIndividual differences in the regulation of positive emotion are associated with psychological resilience and well being. This study investigated the relationship between attachment, self esteem and gender and the regulation of positive emotion. 174 participants completed an online battery measuring attachment avoidance and anxiety, global self esteem and positive emotion regulation strategies (dampening and savouring). Moderating moderation analyses indicated that attachment insecurity was asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
36
2
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 30 publications
(36 reference statements)
8
36
2
3
Order By: Relevance
“…This supports previous connections between insecure attachment and rumination (Lanciano et al, 2012;Reynolds et al, 2014), because our findings suggest that those with higher attachmentbased avoidance scores are thinking negatively about the future. Further, this also relates to the negative mental time travel (i.e., Additionally, other researchers have found an asso ciation between dampening and insecure attach ment, particularly avoidant attachment (Goodall, 2015;Mikulincer & Orbach, 1995). Because dampening is the suppression of positive affect, our findings that avoidance predicts less positive emotions and more negative emotions about the future support these.…”
Section: Positive and Negative Emotions For Future Eventssupporting
confidence: 69%
See 1 more Smart Citation
“…This supports previous connections between insecure attachment and rumination (Lanciano et al, 2012;Reynolds et al, 2014), because our findings suggest that those with higher attachmentbased avoidance scores are thinking negatively about the future. Further, this also relates to the negative mental time travel (i.e., Additionally, other researchers have found an asso ciation between dampening and insecure attach ment, particularly avoidant attachment (Goodall, 2015;Mikulincer & Orbach, 1995). Because dampening is the suppression of positive affect, our findings that avoidance predicts less positive emotions and more negative emotions about the future support these.…”
Section: Positive and Negative Emotions For Future Eventssupporting
confidence: 69%
“…In a study of adolescents, Gentzler et al (2013) found that securely attached individuals reported marginally more savoring than those who were insecurely attached, and Ramsey and Gentzler (2014) found that women acknowledged more savoring than men. Further, insecure attachment has been associated with diminished savoring (Shaver & Mikulincer, 2014), and the dampening SPECIAL ISSUE 2018 PSI CHI JOURNAL OF PSYCHOLOGICAL RESEARCH or repression of positive emotions, particularly for those with avoidant attachment (Goodall, 2015;Mikulincer & Orbach, 1995). Thus, because of the relationship between avoidant attachment and dampening, the experience of joy in positive life events-the focus of the present study-may be more negatively associated with avoidant attachment rather than anxious attachment (see Hypothesis B, below).…”
Section: Psi Chi Journal Of Psychological Researchmentioning
confidence: 99%
“…In discussing this event at a later time, one parent might describe the event but not the related emotions and quickly move on, whereas another parent might ask how the child was feeling and discuss the causes of those emotions and what he did to feel better. This example illustrates the differences in how parents explain causes and consequences of emotions, which can teach the child how to regulate their emotions, which contributes to self‐esteem maintenance (e.g., Goodall, ). Other individual differences include confirming and negating the child's memories, which teaches the child that others have different views from themselves, and elaborating with open‐ended, leading questions, which helps the child connect past, present, and future selves (i.e., creating a personal timeline and coherent self‐esteem; see Fivush, ).…”
Section: Existing Literature On Parental Influence On Self‐esteem In mentioning
confidence: 99%
“…Furthermore, a more complete understanding could be reached by focusing on both partners, rather than studying couple functioning at the individual level. For instance, romantic (i.e., current) attachment insecurity has been linked to maladaptive emotion regulation (Goodall, 2015). However, since several studies suggested that different levels of emotional experience within romantic functioning are affected by gender (Clark, Fitness, & Brissette, 2001), it is still not clear whether gender differences may affect attachment styles and difficulties in emotion regulation strategies in couple relationships.…”
mentioning
confidence: 99%